The Impact of the Work From Home Policy on the Performance of State Civil Apparatus (ASN) in the West Jakarta City Administration Civil Service Agency - Wardhani, Rani Fitra; Kasmir Kasmir (Dinasti Publisher, 2024)
Indonesia implemented a Work From Home policy as an effort to prevent the spread of Covid-19. The Work From Home policy has an impact on environmental ASNs, City Civil Service Agency, Adm. West Jakarta. The aim of the research is to find out the impact of the Work From Home policy on the performance of ASN, as well as solutions to improve the impact of Work From Home in the Municipal Civil Service Administration Sub-district environment. West Jakarta. The research was carried out using qualitative methods by conducting interviews with ASN employees within the City Admin Personnel Agency. West Jakarta. The research results show that the Work From Home policy has an impact on work adaptations and adjustments that must be made. ASN needs to make a work schedule as best as possible according to office hours with the support of a conducive work space. This has an impact on the ability to complete work more quickly because working times are more flexible. However, interaction and coordination between teams decreased because they did not meet face to face. This can be seen in employees who are difficult to contact for coordination. Apart from that, there is a lack of supervision from superiors in monitoring work. So the solution to improve the impact of implementing Work From Home is the need to optimize the use of communication tools, transparent division of work and the need for coordination between members. It is also necessary to create tools that can measure employee performance during the Work From Home period.